Baclofen-Induced Encephalopathy in End Stage Renal Disease - Andrew Meillier; Cara Heller; Shyam Patel (Case Reports in Medicine)
Baclofen is a highly used centrally acting GABA agonist that continues to be an effective therapy for spasticity and chronic hiccups. The renally dependent excretion determines the circulating concentrations and guides effective dosing to decrease adverse reactions. Caution should be considered in administering baclofen to patients with decreased renal function. We present a patient with end stage renal disease on hemodialysis with recent baclofen ingestion who presented with toxic encephalopathy that was resolved with additional dialysis sessions.